The Development of Moisture Sensitivity Test for Compacted Asphalt - Shamshuddin, M.K.; Abdullah, M.E.; Rhasbudin Shah3, S.M. (International Journal of Integrated Engineering, 2011)
Moisture damage is one of the major issues in asphalt distress. It is due to the adhesive andcohesive failure of asphalt mixture and it will shorten pavement life. Moisture-sensitivemixtures need to be identified during the course of the mixture design process which fulfillsthe specified minimum standard. The laboratory testing procedures currently available forcompacted Hot Mix Asphalt (HMA) to test the moisture sensitivity were primarily developedto determine the degree of resistance to moisture damage by a particular combination ofasphalt and aggregate. These moisture sensitivity tests evaluate the effect of moisture damagein laboratory by measuring the relative change of a single parameter before and afterconditioning (i.e., Tensile Strength Ratio, Resilient Modulus Ratio). The tests were simple toconduct and widely accepted by various state and federal agencies, but their drawback includethe empirical nature of the procedures, the dependence of the results on the moistureconditioning methodology and in several cases, the poor correlation with field performance.Many new approaches were conducted to overcome the weaknesses of the existing method.These new approaches mostly designed to conduct the test as close as the field condition andconsider the material properties of asphalt to give the useful result for the asphaltperformance. For better asphalt mixture design, it needs to have the test procedure whichconsidered the effect of traffic loading. The moisture conditioning methodology should avoidusing the vacuum saturation method since this method contributes to the asphalt mixturestrength. The scale of performance measurement can be conducted either microscale ormacroscle. Besides that the test also must be repeatable, reproducible, feasible, practical, andeconomical enough that it can be included in routine asphalt mixture design practice.